La thématique du voyage et la figure du poète-voyageur dans l'œuvre de Venance Fortunat : entre rhétorique, poétique et construction de soi - Herbert de la Portbarré-Viard, Gaëlle (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 2017)
Abstract The theme of the journey and the figure of the poet-traveller hold an important place in the poetic work of the Christian and Italian poet Venantius Fortunatus who came to Gaul in the 560s, in the Merovingian period, where he was to spend the rest of his life. In the Carmina and in Vita Martini, apart from the importance of the rhetoric, spiritual and meta-poetic topos of the poet-traveller, generic variations on the theme of the journey must be added, since this can take the form of a letter, elegy or even an epic. The theme of the journey in Fortunatus culminates in the book relating the journey which completes the Vita Martini: the book indeed concludes by the return to Italy which Fortunatus never lived to see again. Hence, the theme of the journey in Fortunatus is as much involved in a self-building as in the execution of a poetic work in which the figure of the poet-traveller may be one of the keys. [Transl. by the Redaction]